Peril in the Ponds : Deformed Frogs, Politics, and a Biologist's Quest - Helgen, Judith Cairncross (Book collections on Project MUSE., 2012)
'Peril in the Ponds' tells the story of a government biologist's investigation into the mystery of deformed frogs, an epidemic that grew during the 1990s and continues today. It provides an inside view of a highly charged environmental issue that aroused the attention of the public and the media and sparked controversies among scientists, politicians, and government agencies.